Islam and Social Integration in the Reflection of the Nusantara Society - SURYO EDIYONO (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2017)
Religion as a living reality of praxis system reflects the power of flexibility, appreciation and accommodation of growing traditions and cultures. Social inte-gration is the social process of a particular member of society regardless of the cultural and religious diversity embraced, they are aware of the obligation to build solidarity based on strong relationships in building the nation. The process of social integration can work well if supported by good social norms and cus-toms. Social norms and customs are the elements governing behavior and de-manding how cultured Muslim societies behave. This research is designed using descriptive approach that aims to create a description or description systemati-cally, factually, and accurately about the facts, properties, and relationships be-tween the phenomena studied. The results of this study indicate that social inte-gration in Islam is often found in people who view Islam as an understanding that can be compatible with the values of local tradition, this concept is known as Cultural Islam. Cultural Islam is a process in which external elements are ac-cepted by local elements or vice versa. Indonesian clerics have managed to inte-grate Islam and keindonesiaan, so that regional traditions with restrictions that are adjusted to Islamic values.